Structural Analysis of Alkaline Pretreated Rice Straw for Ethanol Production. (15th August 2017) - Phitsuwan, Paripok; Permsriburasuk, Chutidet; Baramee, Sirilak; Teeravivattanakit, Thitiporn; Ratanakhanokchai, Khanok
Abstract : Rice straw (RS) is an abundant, readily available agricultural waste, which shows promise as a potential feedstock for Asian ethanol production. To enhance release of glucose by enzymatic hydrolysis, RS was pretreated with aqueous ammonia (27% w/w) at two pretreatment temperatures: room temperature and 60°C. Statistical analysis indicated similarity of enzymatic glucose production at both pretreatment temperatures after 3-day incubation. Chemical composition, FTIR, and EDX analyses confirmed the retention of glucan and xylan in the pretreated solid, but significant reduction of lignin (60.7% removal) and silica. SEM analysis showed the disorganized surfaces and porosity of the pretreated RS fibers, thus improving cellulose accessibility for cellulase. The crystallinity index increased from 40.5 to 52.3%, indicating the higher exposure of cellulose. With 10% (w/v) solid loadings of pretreated RS, simultaneous saccharification and fermentation yielded a final ethanol concentration of 24.6 g/L, corresponding to 98% of maximum theoretical yield. Taken together, aqueous ammonia pretreatment is an effective method to generate highly digestible pretreated RS for bioethanol production and demonstrates potential application in biorefinery industry.